PERUBAHAN STRUKTUR DAN TIPOLOGI EKONOMI KABUPATEN SAMBAS - ME, sri mulyati (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT The title of this research is the changes of economic structure and typology in Sambas district. Real economic growth followed by rapid price change sine achsector of the economy resulted the changes in the economic structure from year to year. The level of economic growth of aregion, dependingon the natural resources and human resources and supported by external factors such as government policies and targeted the right areas. The purposes of thi sstudy were: (1). toassess changes in the economic structure in Sambas district in the period 2002-2010, (2). to find out which economic sectors are priority and potential for the development in Sambas district. This study uses secondary data. Where the secondary data obtained from Sambas Book Yearbook, Yearbook Kalbar Central Bureau of Statistics for the nine years from 2002-2010 observations. Analysis tool used are Shift-share, Growth-Ratio Model and KlassenTypologi. The results showed that economic sectorsin Sambas district do not have agood performance and none of these sector swhich are dominant growth to the economic sectors of West Kalimantan Province. Mean while the economic sectors that can be prioritized for the development in Sambas district are agriculture and trade, hotel and restaurant. This is due toon this sector has a very large of employment so that unemployment can be reduced. Keywords: economy, economic structure, and economic typology